The twelve principles of CO2 Chemistry - Poliakoff, Martyn; Leitner, Walter; Streng, Emelia S. (Royal Society of Chemistry, 2015)
This paper introduces a set of 12 Principles, based on the acronym CO2 CHEMISTRY, which are intended to form a set of criteria for assessing the viability of different processes or reactions for using CO2 as a feedstock for making organic chemicals. The principles aim to highlight the synergy of Carbon Dioxide Utilisation (CDU) with the components of green and sustainable chemistry as well as briefly pointing out the connection to the energy sector.